Status Harta Waris terhadap Anak Angkat Perspektif Adat Jawa dan KHI - Ahmad Hafid Safrudin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
The presence of adopted children in the family allows for a high level of emotional bonding, which no longer separates one another. So, in time the adopted child can be counted as the person who deserves the property of foster parents after death. This is the result of what happened in the later days. In relation to the problem in this study, that the existence of the adopted child above has a position on the inheritance of treasures. According to Javanese customary law, although the child's appointment does not decide the child's relationship with the parent and adopted child does not become the child of the adoptive parents, but the adopted child is entitled to the inheritance of both the parents and the adoptive parents. Under Islamic law, although it is clear that Islam cannot accept the existence of an adopted child on his or her position on the inheritance of adoptive parents. However, KHI which is a legal written law that is applied as a special guideline for Muslims in resolving all legal issues including the position of the adopted child, in article 209 KHI explained that the adopted child is entitled to receive a testament of a general order of 1/3 from the heritage property of foster parents